Youth and the Cult of Youth? - Smolík, Josef (Kultura-Społeczeństwo-Edukacja, 2014)
This text deals with one of the neglected topics of contemporary social pedagogy which extends to developmental psychology and sociology. This topic is so-called cult of youth which is often mentioned in the academic literature, but has not been precisely conceptualized. This text was therefore focused on the definition of basic category, i.e. youth, and then discussed the relationship to the cult of youth and the individual elements that helps to form it. The cult of youth is associated with so called youth culture, which has been spread and produced by global media. The influence of the media has been already evident from the 60’s of the 20th century, when we often talk about American cultural hegemony which presents within its production the popular culture and youthful lifestyle, which is then presented in magazines, music media, fashion industry, etc. For contemporary capitalist society the concept of the cult of youth is a useful concept as only successful, young and efficient individuals can consume new and new products (as well as use the services) typical for this still-rising imaginary phase of human life. Therefore the cult of youth is the domain of successful people who do not want to lose their success. Only socially successful can try to be “forever young”.